Criminal procedure - Rolando V Del Carmen
This eminently practical text has become a market leader as a result of its succinct, clear writing style, extensive use of engaging pedagogy, and unique ability to cover procedure completely and correctly without bogging students down in minutiae. Filled with case briefings, examples, sample police forms, and the most recent Supreme Court rulings, this book is known for its relevance to law enforcement officials and professionals in the field